Triumphal Arch, Golden Gate International Exposition, San Francisco (H.S. Crocker Co., Inc.)
Triumphal Arch between the Court of Reflections and the Court of the Flowers at the 1939 Golden Gate International Exposition on Treasure Island in San Francisco Bay.